Paroxismo (2016)
"We live in a society of ephemeral happiness, of perpetual euphoria, of eternal availability, where the slightest demonstration of negative emotionality is considered not only inappropriate but also evidence of bad character. This inability to demonstrate negative emotions has resulted in their repression when they arise, and when we can no longer hide them when they boil and overflow without control, we dont know how to handle them... We need to use negative emotions as the human tools they are, of living and experiencing them without social pressure or personal stigmas, of escaping the domestication, conformity and security guaranteed socially by rejecting them." -- Tomado del Formato de Documento de Grado.